Binocular Diplopia Treated with Inferior Rectus Recession and Faden Operation of The Normal Eye in a Case of Blow Out Fracture - Smita Kapoor; V. Rajesh Prabu; Swarna Udayakumar (Delhi Journal of Ophthalmology)
We report a case of right eye inferior rectus palsy following blow out fracture repair in a 11-year- old boy. The blow out fracture repair was done 2 weeks following trauma. On presentation, the patient was orthotropic in primary gaze with diplopia in downgaze. Cover test revealed (OD) hypertropia and (OS) hypotropia. Prism bar cover test showed maximum hypertropia in depression and dextrodepression. Diplopia charting also revealed maximum separation of images in dextrodepression. Computerized tomography was performed which suggested edema and thickening of (OD) inferior rectus muscle with no entrapment. The patient underwent (OS) 3mm inferior rectus recession and Faden operation (15mm), following which, he was diplopia free on post operative day1, at 1 and 6 months followup. Faden operation (posterior fixation suture) with or without inferior rectus recession of the other eye is a surgical option for inferior rectus palsy.